Allergen immunotherapy in atopic dermatitis: Light and shadow in children. (24th November 2020) - Caminiti, Lucia; Panasiti, Ilenia; Landi, Massimo; De Filippo, Maria; Olcese, Roberta; Ciprandi, Giorgio; Vernich, Mario; Carelli, Francesco; Votto, Martina; Barberi, Salvatore
Abstract: Atopic dermatitis (AD) is a chronic remitting‐relapsing inflammatory skin disorder. Due to the multifactorial pathogenesis, there are numerous therapeutic management approaches, mainly based on symptomatic treatments. In recent years, allergen immunotherapy (AIT) has been progressively advanced as targeted disease‐modifying treatment of allergic disease. The most recent guideline from the American Academy of Dermatology concludes that data available do not support its use in AD. The Joint Task Force and The European Academy of Dermatology suggest that clinicians can consider AIT treatment in selected patients characterized by aeroallergen sensitization, prevalently HDM, severe AD, and clinical exacerbation after exposure to the causative allergen. Nevertheless, its role in AD is still under debate, especially in children.